Dinner with Edward [large type] : the story of a remarkable friendship - Vincent, Isabel, 1965- (Thorndike Press, a part of Gale, Cengage Learning, 2016)
When Isabel meets Edward, both are at a crossroads: he wants to follow his late wife to the grave, and she is ready to give up on love. While helping Edward's faraway daughter by checking on her nonagenarian dad, Isabel has no idea that he will end up changing her life.